Is corporate social responsibility an industry sensitive phenomenon? (KASBIT Business Journal, 2022)
Through content analysis, this study is conducted to observe the understanding level, implementation stage and disclosure route/intensity within various nature of corporations operating in Pakistan. GRI (G-4) guidelines were taken to calculate the CSR’s trends within sin and neutral industries. Overall, this research revolves around the extent of different CSR’s dimensions, essence of its indicators and the nature of activities both in more and less sensitive (hazardous) corporations. Unlike proposition, it was noticed that neutral industries outperformed in almost every dimension. Government and other law enforcement institutions should act as watchdogs to monitor corporate activities, especially in sin industries. They should introduce and implement customized CSR guidelines which are not only acceptable to corporations but also fulfill the needs and priorities of all stakeholders, especially weak and silent stakeholders.
Keywords: Corporate social responsibility; neutral industry; sin industry; GRI (G-4); Pakistan